Fabrication of space: The design of everyday life in South Korean Songdo. (March 2023) - Bartmanski, Dominik; Kim, Seonju; Löw, Martina; Pape, Timothy; Stollmann, Jörg
Constructed from scratch on land reclaimed from the sea, Songdo was planned to embody new 'smart city' life. In reality, it has come to exemplify enclave urbanism that commodifies securitised living for upwardly mobile middle classes. While the political economy of this urban project is by now well studied, the sociological ethnography of the resultant space and its experiential correlates remains less developed and imperfectly contextualised. One needs to connect the dots of power and space. The present paper aims to do that and thematises the 'design of everyday life' which rests on (1) the intensification of privatised digital surveillance of mass housing compounds which in turn occasions (2) the remaking of spatial markers and symbolic boundaries between private/public, inclusive/exclusive, inside/outside. As such it is a combination of two different registers of visibility that gets jointly orchestrated by the public–private partnership of Korean state and corporate actors. In order to recognise these regimes as strategic visions of controlled social life we extend James Scott's notion of 'seeing like a state' to include the corresponding regime that we call 'seeing like a corporation'. This allows us to show that they are mutually elaborative in Songdo through a hybridised fabrication of its lived environment, particularly in the case of one branded housing typology located in the city's centre called International Business District. This elucidates not only the local entrepreneurial urbanism that gave rise to the controlled environment of Songdo but also more general logics of the 'compressed modernisation' in the region which sets a global mode for production of space and re-territorialisation of power.